ORGANIZATION OF DECISION SUPPORT FOR CRISIS MANAGEMENT - Юдін, О. К.; Фролов, О. В.; Бойко, Ю. П. (Science-based technologies, 2015)
The article presents structural logic schemes of building decision support systems in crisis situations with providing support for video conferencing based on heterogeneous networks. The proposed structural solutions allow implementing them with the use of any data transmission systems of the conditions of implementation of new compression technology based on the presented methods and models of adaptive encoding digital-out the images of preset quality. It is shown that the use of improved compression technology based on the methods for adaptive coding can be definitely implemented on H.32x protocol type platform without additional technical changes or communication equipment replacement and can achieve higher video transmission speed via communication channels.